(untitled) (Orthodontic Journal of Nepal, 2021)
Introduction: Anxiety is the state of feeling nervous or worried that something bad is going to happen. Dental anxiety is defined as a patient’s response to stress that is associated with a dental procedure. The aim of our study is to investigate the anxiety status of dental patients visiting Orthodontic department at Nobel Medical College Teaching Hospital, Biratnagar. Materials and Method: Total 80 ongoing orthodontic patients (M =21 F=59) who completed modified Dental Anxiety Scale questionnaire were included in the study. Result: Majority of patients (65%) had moderate anxiety where as 25% had mild anxiety and around 9% had severe to extreme anxiety. Patients’ age and education level had significant association with the level of dental anxiety. Conclusion: Dental anxiety in orthodontic patients is unavoidable but needs appropriate counseling. Orthodontist’s role is crucial in bridging the gap between patients’ perception towards orthodontic treatment and the actual treatment.